The Potential Efficacy of Thymoquinone and Hesperidin as Prophylaxis for Endotoxin Induced Oxidative Stress in Rats (Bangladesh Journal of Medical Science, 2026)
Introduction This experimental study evaluates the protective effect of Thymoquinone (TQ) and Hesperidin (HSP) as antioxidants on endotoxin Lipopolysaccharide (LPS) induced oxidative stress in rats. Materials and methods Total 56 rats were divided equally into seven groups; each contained eight rats. Group-1 rats served as control, given normal saline orally 14 days; Group-2 and Group-3 rats were given TQ and HSP respectively for 14 days; Group-4 rats were given a single dose LPS intraperitoneally on 14th day; Group-5 and Group-6 rates were given TQ and HSP respectively for 14 days followed by single dose LPS on 14th day; Group-7 rats were given TQ and HSP separately at 10-minutes interval for 14 days followed by single dose LPS on 14th day. After 14 days, rats were sacrificed and biochemical tests on (i) rats’ serum; (ii) rats’ brain tissue, with (iii) histopathology and (iv) immunohistochemistry in brain tissues were assessed among all seven groups. Results LPS induces significant increase in serum corticosteroid, tumor necrosis factor alpha (TNF-α) and decrease in total antioxidant capacity (T-AOC) compared to control group which were reversed with TQ and HSP treated group. Similarly, in brain tissue, LPS induces significantly increased brain Malondialdahyde (MDA), ATP, ADP, Cholesterol, Phospholipid, and significantly decreased Na+K+ ATPase and Superoxide dismutase (SOD) compared to control group which was reversed in TQ and HSP treated group. The histopathology and immunohistochemistry confirm the results. Conclusion Both TQ and HSP complement (synergistic) the antioxidant, antiinflammatory, and anti-apoptotic properties of each other, and have neuroprotective effects against oxidative stress induced by LPS.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 821-831